The effect of intermittent dosing of Nicotiana glauca on teratogenesis in goats. (January 2015) - Welch, K.D.; Panter, K.E.; Lee, S.T.; Gardner, D.R.
Abstract: Sustained inhibition of fetal movement in livestock species, induced by several poisonous plants, can result in numerous skeletal-contracture malformations. Lupines are responsible for a condition in cattle referred to as "crooked calf syndrome" that occurs when pregnant cattle graze teratogenic lupines. Similar malformations are also seen in animals poisoned by Conium maculatum (coniine) and Nicotiana glauca (anabasine). A proposed management strategy to limit these types of birth defects includes utilizing an intermittent grazing schedule to allow short durations of grazing lupine-infested areas interrupted by movement to a lupine-free pasture. The objective of this study was to use a goat model to determine if an intermittent schedule of five continuous days on treatment followed by two days off treatment would be sufficient to decrease, or prevent, the incidence of anabasine-induced malformations. The data from this study suggest that, for N . glauca in goats, the intermittent grazing program of five days exposure with two days of non-exposure is insufficient to prevent significant skeletal malformations from occurring. However, this study did demonstrate an inverse relationship between the amount of serum anabasine in the dam and the extent of fetal movement. Highlights: Nicotiana glauca (anabasine) causes inhibition of fetal movement and subsequent teratogenesis in goats. The mode of action of anabasine-induced skeletal contracture malformations is by inhibition of fetal activity. An intermittent anabasine dosing regimen of five days on, two days off does not prevent skeletal malformations from occurring. There is an inverse relationship between serum anabasine concentration in the dam and fetal movement.